If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(p + 2) = 9 + -1p Reorder the terms: 7(2 + p) = 9 + -1p (2 * 7 + p * 7) = 9 + -1p (14 + 7p) = 9 + -1p Solving 14 + 7p = 9 + -1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'p' to each side of the equation. 14 + 7p + p = 9 + -1p + p Combine like terms: 7p + p = 8p 14 + 8p = 9 + -1p + p Combine like terms: -1p + p = 0 14 + 8p = 9 + 0 14 + 8p = 9 Add '-14' to each side of the equation. 14 + -14 + 8p = 9 + -14 Combine like terms: 14 + -14 = 0 0 + 8p = 9 + -14 8p = 9 + -14 Combine like terms: 9 + -14 = -5 8p = -5 Divide each side by '8'. p = -0.625 Simplifying p = -0.625
| -2x=6/13 | | 2/3x-3/4=5/8 | | J/3-J-3/6=7/6 | | 3(2a+4)=9 | | x/3=0.3333333333333333333333333 | | -3/7y=10 | | 3x=0.9999999999 | | logt-3=log(17-4t) | | 42=x+.4x | | y=12-x^4-6x^3+11x^2 | | 5x-57=98 | | 4x+5y=1115 | | 2c+5=c-8 | | 6x+5y+6z-3x+2z=-7y | | 7=7-7 | | 13-4x=21-6x | | 8f+19=14 | | 0=3x^2+13x+4 | | (1+v)(5v+7)=0 | | -3(r+6)=-41 | | 3x-7-7x=5 | | f(x)=3cosx | | 5.3=9.3-0.5x | | 0=20t-4.9t^2 | | x/6=12/15 | | 2(2x-i)4x-6x= | | 4a+2b-6a+3a= | | 37.12=8g+3.84 | | (x-8)2/3=4 | | 5y+30=3x | | 3x-6/4=12 | | v^2-2v-5=0 |